Penentuan Tingkat Kebisingan Pada Area Pengolahan Sekam Padi, Siltstone Crusher, Cooler Dan Power Plant Pada PT Lafarge Cement Indonesia-Lhoknga Plant - Juliansyah Harahap (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
This research conducted in PT. Lafarge Cement Indonesia which is one of company whose field in cement production located in western Indonesia region, exact place in Aceh province. The aimed of this research are to know about noise levels in some production areas of PT. Lafarge Cement Indonesia Lhoknga plant and define anticipation actions to the effect of existing noice level based on Hierarchy of Control (HoC). Used method in this research are measuring method with sampling points where measurement conducted if the noise suspected over the threshold limit by conducting noise sampling just onto one or few locations. Sample data obtained then being processed and analized by using statistical method. The result of this research concluded that rice husk processing area, siltstone crusher, cooler and most of power plant area which is in front of condenser 1 and 2, and near to turbin 1 and 2 have LAeq value over than 85 dB so that using hearing protection is a mandatory. Control conduct to the over noise shelf in few areas can be conducted by implementing HoC like elimination, substitution, engineering control (redesigning equipment, servicing and maintaining equipment, isolating equipment, damping and cushioning noise source and installing absorbtive baffles), administrative control (work hours per day limitation and health surveillance program) and using tools for self protection (application of hearing protection with NRR which can cover the noise shelf to workers).